The bidirectional relationship between endometriosis and microbiome - Uzuner, Cansu; Mak, Jason; El-Assaad, Fatima; Condous, George (Frontiers in Endocrinology, 2023)
Endometriosis has been described by many different theories of pathogenesis over the years. It is now also appreciated to be a state of chronic inflammation, and the role of immune dysfunction in its development has been proven. There is increasing evidence to support the role of the microbiome in the formation and progression of endometriosis via these inflammatory pathways. The dysbiosis seen in endometriosis is thought be both causative and the product of the disease. Gut, peritoneal fluid and female reproductive tract microbiota has been studied to understand if there are any microbiome signatures specific to endometriosis. New research on how to manipulate the microbiome for better detection and treatment of endometriosis is emerging.